STUDI FENOMENOLOGI TENTANG PENGALAMAN KOMUNIKASI ANTAR PRIBADI ORANG TUA-ANAK TERHADAP PEMAHAMAN ANAK PADA NORMA-NORMA PERILAKU (KASUS PADA ANAK PENYANDANG AUTISME) - Desi Dwi Prianti (Program Studi Ilmu Komunikasi FBIK Unissula, 2011)
Interpersonal Communication is the most important communication process for every human being. Family relationship is one of the examples where interpersonal communication happened between Parents and Child. Moreover, family is the most important â€œsocial networkâ€ for a child in their early life period so that relationship with family is a kind of base attitude to other people, things and life in general. Therefore interpersonal communication between parents and child has, a role in giving child understanding about the way of life that child must internalize through behavior norms that have been taught. On the other hand, autism disorder severely impairs development of a personâ€™s ability to communicate both verbal and nonverbal, interact with other people, and maintain normal contact with the outside world. This condition needs serious attention for parents with autism child. The purpose of this research is to reveal about how interpersonal communication happened between parents and child in giving understanding about behavior norms to autism child. Theories that used in this research are interpersonal communication theories from Devito, Laing and Fisher, effectiveness interpersonal communication theory from humanistic perspective, child dependency theory from Jones and Gerard, child communication theory from schramm and phenomenology theory. Research method that used in this research is qualitative descriptive with phenomenology approach. From this research we may know that parents experience in communicating with autism child is different between one to another. Every parentâ€™s interpretation about their experience is being infl uenced by their relation with time, their self, information about autism also child age and child condition. Regarding self in relation to time revealed that the more parents spent their time with their child the more parents understand about their child characteristic and child habit that leads to effectiveness communication. In relation to self revealed that after they knew about their child condition, they show empathy, supportiveness, positiveness in their attitudes. In brief, we can say that the parentsâ€™ willingness to confess that they have autism child is the most signifi cant step, whichhave great impact to their child development.